NON-COMPLIANT PATIENT – ETHICAL VIEWS - SOMEŞAN, Andreea-Iulia (Studia Universitatis Babeş-Bolyai Bioethica, 2018)
Romania is among the top of European countries with the highest prevalence of self-medication. A better understanding of the present management of medical non-compliance could have a contribution in understanding and improving, from the ethical perspective, of the medical staff’s behaviour for the purpose to reduce this phenomenon. REZUMAT. Pacientul necompliant – Perspective etice. România se află pe locurile fruntașe ale Europei în privința automedicației. O mai bună înțelegere a modului în care este gestionată în prezent necomplianța medicală poate contribui la înțelegerea și îmbunătățirea din perspectivă etică a comportamentului personalului medical cu scopul de a reduce acest fenomen. Cuvinte cheie: automedicația, necomplianța medicală, colaborarea doctor - pacient.